Interpersonal Violence, Emotion Regulation, and Trauma-Coping Self-Efficacy as Predictors of Posttraumatic Stress Disorder, Substance Use, and Risk Engagement Among Women in Jail - Weber, Shelby (Journal of interpersonal violence, 2026)
Women in jail report significantly higher rates of interpersonal violence, posttraumatic stress disorder (PTSD) symptoms, and substance use disorders compared to the general population. Exposure to interpersonal violence is associated with PTSD and maladaptive behaviors such as substance use and engagement in risky behaviors. However, less is known about mechanisms, such as emotion regulation and trauma-coping self-efficacy, that might increase or decrease the likelihood of these maladaptive behavioral health outcomes in this population. The present study investigated the extent to which emotion regulation and trauma-coping self-efficacy exert indirect effects on the relations between cumulative interpersonal violence exposure and distress outcomes (i.e., PTSD, substance use, and risky behavior) among women in jail. Interviews were completed by 180 randomly selected women recruited from two county detention centers in the Mountain Northwest. Hypotheses were tested using structural equation modeling. Interpersonal violence significantly predicted PTSD, risky behaviors, difficulties in emotion regulation, and trauma-coping self-efficacy. Difficulties with emotion regulation predicted PTSD and trauma-coping self-efficacy predicted PTSD and substance use symptoms. In addition, there were significant indirect effects for both emotion regulation and trauma-coping self-efficacy on interpersonal violence and PTSD and interpersonal violence and substance use. These findings suggest potential targets for intervention in the underserved and highly trauma-exposed population of system-involved women.